Introduction of water footprint assessment approach to enhance water supply management in Malaysia - Syazwan, N. Moni; Edriyana, Abd Aziz; Marlinda, A. Malek (AIP Publishing, 2017)
Presently, Water Footprint (WF) Approach has been used to assess the sustainability of product’s chain globally but still lack in services sector. Thus, this paper aims to introduce WF assessment as a technical approach to determine the sustainability of water supply management for the typical water supply treatment process (WSTP) used in Malaysia. Water supply is one of the pertinent services and most of WF accounting begin with data obtained from water supply treatment plant. Therefore, the amount of WF will be accounted for each process of WSTP in order to determine the water utilization for the whole process according to blue, green and grey WF. Hence, the exact amount of water used in the process will be known by applying this accounting method and the sustainability of water supply management in Malaysia will be able to assess. Therefore, the WF approach in assessing sustainability of WSTP will be able to be implemented.